Glutathione administration reduces the DNA fragmentation index in sperm preparation with the Swim-Up (SU) and mini-Density Gradient Centrifugation (mini-DGC) methods at Doctor Soetomo General Hospital, Surabaya, Indonesia - Lutfi Hardiyanto; Amarudin Amarudin; Indra Gusti Mansur; Supardi Supardi; Wahyuning Ramelan; Hamdani Lunardhi (Intisari Sains Medis, 2020)
Background: Spermatozoa requires Reactive Oxygen Species (ROS) in physiological quantities for capacitation for fertilization purposes. However, if the balance between ROS production and antioxidant capacity is disrupted, it can result in oxidative stress, negatively affecting chromatin spermatozoa, leading to male infertility. This study evaluates the glutathione administration reduces the DNA fragmentation index in sperm preparation with the Swim-Up (SU) and mini-Density Gradient Centrifugation (mini-DGC) methods at Doctor Soetomo General Hospital, Surabaya, Indonesia.Methods: A true experimental study by post-test only control group was conducted using ejaculate fluid of 9 infertile patients with normozoospermic at the Department of Medical Biology, Faculty of Medicine, Universitas Indonesia, Jakarta in January - February 2019 period. The spermatozoa DNA fragmentation was examined by following the instructions for using Spermfunc® DNAf Kit for Determination of the DNA Fragmentation Level in Spermatozoa by Sperm Chromatin Dispersion (SCD) for both preparation methods. Data were analyzed using SPSS version 16.0 for Windows.Results: SU vs. SU+glutathione method gave a lower but insignificant DNA fragmentation effect (p>0.05). The mini-DGC vs. mini-DGC+glutathione method showed significant results (p<0.05). SU+glutathione vs mini-DGC+glutathione showed no significant results (p>0.05). Meanwhile, the SU vs. mini-DGC method showed significant results (p <0.05). The recovery rate (RR) of the mini-DGC method has a higher value and is even better if glutathione is given compared to the SU method.Conclusion: Spermatozoa preparation in the SU method gives a lower DNA fragmentation effect than the mini-DGC method. The administration of glutathione can be a particular consideration in carrying out spermatozoa preparation to protect spermatozoa from damage during preparation.